2019
DOI: 10.2147/ott.s224881
|View full text |Cite
|
Sign up to set email alerts
|

<p>Exosomes-Derived Long Non-Coding RNA HOTAIR Reduces Laryngeal Cancer Radiosensitivity by Regulating microRNA-454-3p/E2F2 Axis</p>

Abstract: BackgroundStudies have revealed exosomes are implicated in tumor microenvironment and tumorigenesis. Emerging evidence suggests long non-coding RNAs (lncRNAs) possess pivotal roles in laryngeal cancer progression. For this study, we aimed to find out the mechanism of exosomes and lncRNA HOTAIR in laryngeal cancer.MethodsLaryngeal cancer cells-derived exosomes were initially extracted, separated and identified. Flow cytometry was applied to detect apoptosis to evaluate the effect of exosomes on cell radiosensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
(35 reference statements)
3
16
0
Order By: Relevance
“…In this study, LINC00261 was mainly located in the cytoplasm of ESCC cells by subcellular separation assay, illustrating that LINC00261 might modulate its downstream gene expression after transcription. Bioinformatics websites predicted the target gene of LINC00261 and identified miR-545-3p which has been reported to exert major roles in multiples cancers, such as non-small-cell lung cancer cells , hepatocellular carcinoma (Changjun et al, 2018), and laryngeal cancer (Cui et al, 2019). Our present study verified that LINC00261 served as a ceRNA for miR-545-3p and negatively regulated miR-545-3p expression.…”
Section: Discussionsupporting
confidence: 76%
“…In this study, LINC00261 was mainly located in the cytoplasm of ESCC cells by subcellular separation assay, illustrating that LINC00261 might modulate its downstream gene expression after transcription. Bioinformatics websites predicted the target gene of LINC00261 and identified miR-545-3p which has been reported to exert major roles in multiples cancers, such as non-small-cell lung cancer cells , hepatocellular carcinoma (Changjun et al, 2018), and laryngeal cancer (Cui et al, 2019). Our present study verified that LINC00261 served as a ceRNA for miR-545-3p and negatively regulated miR-545-3p expression.…”
Section: Discussionsupporting
confidence: 76%
“…The cells were observed under a dissecting light microscope (magnification, ×100), and the colonies containing >50 cells were counted. The survival fraction (SF) were calculated as follows: SF = (number of colonies/number of cells plated) irradiated /(number of colonies/number of cells plated) non-irradiated ( 30 ) The SF in each group was also analyzed using GraphPad Prism 5.0 (GraphPad Software, Inc.) as previously described ( 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…microRNAs are involved in multiple biological processes, including cellular differentiation, proliferation, and apoptosis 34,35 . Previous studies have demonstrated that miR‐545‐3p affects the pathogenesis of various cancers 36–38 . miR‐545‐3p was shown to be elevated in H/R‐induced H9C2 cells and the overexpression of miR‐545‐3p significantly down‐regulated the apoptosis of H9C2 cells.…”
Section: Discussionmentioning
confidence: 99%